-x+4(-5x+3)=-2(-6+3x)

Simple and best practice solution for -x+4(-5x+3)=-2(-6+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+4(-5x+3)=-2(-6+3x) equation:


Simplifying
-1x + 4(-5x + 3) = -2(-6 + 3x)

Reorder the terms:
-1x + 4(3 + -5x) = -2(-6 + 3x)
-1x + (3 * 4 + -5x * 4) = -2(-6 + 3x)
-1x + (12 + -20x) = -2(-6 + 3x)

Reorder the terms:
12 + -1x + -20x = -2(-6 + 3x)

Combine like terms: -1x + -20x = -21x
12 + -21x = -2(-6 + 3x)
12 + -21x = (-6 * -2 + 3x * -2)
12 + -21x = (12 + -6x)

Add '-12' to each side of the equation.
12 + -12 + -21x = 12 + -12 + -6x

Combine like terms: 12 + -12 = 0
0 + -21x = 12 + -12 + -6x
-21x = 12 + -12 + -6x

Combine like terms: 12 + -12 = 0
-21x = 0 + -6x
-21x = -6x

Solving
-21x = -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-21x + 6x = -6x + 6x

Combine like terms: -21x + 6x = -15x
-15x = -6x + 6x

Combine like terms: -6x + 6x = 0
-15x = 0

Divide each side by '-15'.
x = 0

Simplifying
x = 0

See similar equations:

| 1/5x^2=x-4/5 | | 2x+10x=-5+2x | | sin4x=(root3)/2 | | sin4x=root3/2 | | 2(c+6)=-2(x-4) | | 30-2x=6x+6 | | 3+9=-3(8x-4) | | 1K/3-4k/3= | | 3b-2(-5b+3)=12-5b | | 3b-2(5b+3)=12-5b | | 28x+4y=8 | | K/3-4k/3= | | 19x+11y=20900 | | 20=2(6)-8 | | -6(5k+4)=-114 | | 8.92x/133.8=(7.17)(35.85) | | 2x-8=2x-8 | | 36=3y-15 | | 6x^5/4x | | 2.5x^2=3x | | -16-3x=5-6x | | .11x+.05(7500-x)=675 | | 2+3(6)= | | 5ln(5x+2)=22 | | 2=m^2-7 | | 5×5/6 | | Y=0.002x+0.000 | | -4x+3=-5x-4 | | 3(11x-7)=13+25 | | 3x/2-x/3=5(x-4)/6 | | 64x+44=-20 | | 64x+4=-20 |

Equations solver categories